Response to lower dose TNF inhibitors in axial spondyloarthritis; a real-world multicentre observational study. Issue 2 (13th May 2020) - Van Rossen, Liz; Chan, Antoni; Gilbert, Annie; Gaffney, Karl; Harris, Claire; Machado, Pedro M; Santos, Liliana R; Sengupta, Raj; Basset, Paul; Keat, Andrew
Abstract: Objective: Dose optimization of TNF inhibitors in axial spondyloarthritis (axSpA) is attractive, but it is unclear for which patients this approach might be appropriate. Methods: Seventy-one patients with axSpA, from six UK centres, were identified who had reduced their dose of TNF inhibitor after being considered to be stable responders. All completed a questionnaire concerning their approach to and experience of dose reduction. Data on patient characteristics, metrology and CRP were retrieved retrospectively from patient records. Results: Over 2 years of observation, 60 (84.5%) remained (REM) on reduced-dose medication and 11 (15.5%) reverted (REV) to the original dose. The overall mean dose reduction was 39% for REM patients and 44% for REV patients. Both groups initially responded in a similar manner to treatment, but the data showed a trend that younger women were more likely to revert. Neither BMI nor smoking was associated with continued low-dose responsiveness. Eight of the 11 REV patients reverted by 6 months. None reached criteria of secondary drug failure, and all regained control after increasing back to the original dose. Most patients in both groups reached the decision to reduce the dose jointly with clinicians. A preference for taking the reduced dose was not associated with low-dose drug survival. Conclusion: Many patients with axSpA remain well symptomatically after stepping down the dose of TNF inhibitor, but young women are less likely to do well on a reduced dose. Dose reduction should be one element of the management of patients with axSpA.